Nonlinear Finite Element Analysis of Steel Fiber Reinforced Concrete Deep Beams With and Without Opening (Journal of Engineering, 2012)
This paper presents a nonlinear finite element modeling and analysis of steel fiber reinforced concrete (SFRC) deep beams with and without openings in web subjected to two- point loading. In this study, the beams were modeled using ANSYS nonlinear finite element software. The percentage of steel fiber was varied from 0 to 1.0%.The influence of fiber content in the concrete deep beams has been studied by measuring the deflection of the deep beams at mid- span and marking the cracking patterns, compute the failure loads for each deep beam, and also study the shearing and first principal stresses for the deep beams with and without openings and with different steel fiber ratios. The above study indicates that the location of openings and the amount steel fiber are affects to the behavior and strength of deep beams. And also when the results of the experiments taken from the literature were compared with the results obtained from the beam modeled with ANSYS finite element program, it was shown that the results of computer model gave similar results to the experimental behavior.